An Ethnographic Study of Visitor Motivations for Attending Flow Festival - Berberoglu, Emre (fi=Turun yliopisto|en=University of Turku|, 2018)
Since their origins in the 17th century, festivals have been important cultural events that kept members of communities together by celebrating their values and ideologies. Over the last couple of decades, the meaning of music festivals, demands and needs of attendees, and festivals’ impact on cultures and societies have altered significantly. Due to complex and multi-layered motivation structure of attendees, today’s music festivals offer unique attractions for their visitors. The aim of this study is to comprehend the motivational structure of Flow Festival attendees and their influence over the way festival is organized. Ethnographic interviews with Flow festival attendees and the managing director of the festival will set up the main data of this study. By adopting the “leisure motivation theory” and “motivational domain concept”, the study will explore motivation and demotivation of festival attendees of Flow Festival. Furthermore, utilization of participatory culture theory will assist the study to achieve a deeper understanding of the impact Flow Festival attendees’ motivation and demotivation have over the festival’s organizational aspects. The study concludes that motivation and demotivation of Flow Festival attendees have shaped the organizational structure of the festival through feedback and participation. Moreover, the research illustrated that while demotivation of Flow Festival attendees had an instantaneous influence over the organizers, motivation affected organizational plans in the long run.